Profile of blood cells and inflammatory mediators in periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome - Brown Kelly L; Wekell Per; Osla Veronica; Sundqvist Martina; Sävman Karin; Fasth Anders; Karlsson Anna; Berg Stefan (BMC, 2010)
Abstract Background This study aimed to profile levels of blood cells and serum cytokines during afebrile and febrile phases of periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome to advance pathophysiological understanding of this pediatric disease. Methods A cohort of patients with a median age of 4.9 years experiencing 'typical PFAPA' episodes participated in this study. Blood cells and serum cytokines were analyzed by CBC analysis and multiplex ELISA. Results Oscillations in the concentration of blood cells during the afebrile and febrile phases of typical PFAPA syndrome were observed; novel findings include increased monocytes and decreased eosinophils during a febrile episode and increased thrombocytes in the afebrile interval. Relatively modest levels of pro-inflammatory cytokines were present in sera. IFNγ-induced cytokine IP10/CXCL10 was increased after the onset of fever while T cell-associated cytokines IL7 and IL17 were suppressed during afebrile and febrile periods. Conclusions Identification of dysregulated blood cells and serum cytokines is an initial step towards the identification of biomarkers of PFAPA disease and/or players in disease pathogenesis. Future investigations are required to conclusively discern which mediators are associated specifically with PFAPA syndrome.